1999
DOI: 10.1007/s005340050120
|View full text |Cite
|
Sign up to set email alerts
|

p53 Gene mutations and overexpression of p53 product in cancerous and noncancerous biliary epithelium in patients with pancreaticobiliary maljunction

Abstract: To investigate the molecular mechanisms of the high incidence of carcinogenesis in the biliary epithelium of patients with pancreaticobiliary maljunction, we examined p53 gene mutations, loss of heterozygosity of p53, and overexpression of p53 gene product in the cancerous and noncancerous biliary epithelium of 27 patients with pancreaticobiliary maljunction. Mutations of the p53 gene were examined by polymerase chain reaction-single strand conformation polymorphism and a direct sequencing method. Loss of hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
5
27
0
3
Order By: Relevance
“…14 Multicentric development of biliary carcinoma may occur in patients with PBM, and mutations of oncogenes, such as K-ras, 15,16 and tumor-suppressing genes, such as p53, 17 are detected in noncancerous biliary epithelium with hyperplasia, metaplasia, and even inflammation before neoplastic changes were histologically detected. In the present case, chronic inflammation of the bile duct due to PBM could first lead to metaplasia, resulting in an increase in the number of Kulchitsky cells that acted as a predisposing factor for the development of neuroendocrine carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…14 Multicentric development of biliary carcinoma may occur in patients with PBM, and mutations of oncogenes, such as K-ras, 15,16 and tumor-suppressing genes, such as p53, 17 are detected in noncancerous biliary epithelium with hyperplasia, metaplasia, and even inflammation before neoplastic changes were histologically detected. In the present case, chronic inflammation of the bile duct due to PBM could first lead to metaplasia, resulting in an increase in the number of Kulchitsky cells that acted as a predisposing factor for the development of neuroendocrine carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 A number of EBDCs arise in bile ducts with an abnormal pancreatico-biliary duct junction, and their tumorigenesis is considered to be associated with inflow of pancreatic juice into the bile duct. [4][5][6][7] However, more common mechanisms for the tumorigenesis and the reasons for the biological aggressiveness of EBDCs have not yet been sufficiently elucidated, and further investigations are required.…”
mentioning
confidence: 99%
“…Gallbladder carcinomas associated with APBDJ present the highest prevalence of K-ras mutation, suggesting that the pancreatic juice reflux may constitute a risk factor for the development of GC [9,11]. It has also been reported that K-ras mutation at codon 12 is associated with early stage gallbladder carcinoma with APBDJ than in that without APBDJ [30].…”
Section: K-ras Oncogenementioning
confidence: 94%
“…A third pathway involving an anomalous pancreaticobiliary duct junction (APBDJ), determined as hyperplasia-carcinoma sequence, occurs frequently in East Asia (incidence 0.9-3.2% in Japan) [7,8] and is characterized by a higher incidence of K-ras gene mutations than that observed in carcinomas without APBDJ [9,10], and high incidence of p53 mutations [10,11]. The involvement of an alternative molecular pathway, that of microsatellite instability (MSI) (i.e., the length alterations at simple repetitive sequences throughout the genome), has been established in the development of certain gastrointestinal neoplasms, such as colorectal and gastric.…”
Section: Introductionmentioning
confidence: 99%